Review article: chronic liver disease and pregnancy. Issue 3 (29th June 2020) - Faulkes, Rosemary E.; Chauhan, Abhishek; Knox, Ellen; Johnston, Tracey; Thompson, Fiona; Ferguson, James
Summary: Background: The prevalence of chronic liver disease in women of child bearing age is increasing, leading to a higher incidence of pregnancy in this cohort. Chronic medical conditions have a significant adverse effect on maternal morbidity and mortality. To date, reviews on this topic have been written either from a hepatology or obstetrics viewpoint, and no specific guidelines are available solely for the management of chronic liver disease in pregnancy. Aims: To produce a comprehensive review on the clinical management of women with chronic liver disease during pregnancy, addressing the risks of pregnancy to mother and child, how these risks can be ameliorated, and what additional considerations are required for management of chronic liver disease in pregnancy. Methods: Data were collected up to May 2020 from the biomedical database PubMed, national and international guidelines in gastroenterology and hepatology. Results: During pregnancy, women with cirrhosis are more likely to develop decompensated disease, worsening of portal hypertension, and to deliver premature infants. Conclusions: The risks associated with pregnancy can be ameliorated by advanced planning, assessing risk using the model for end stage liver disease score and risk reduction through varices screening. A multidisciplinary approach is paramount in order to minimise complications and maximise the chance of a safe pregnancy and birth for mother and baby.